2022
DOI: 10.1021/acsnano.1c09136
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional CIPS-InSe van der Waal Heterostructure Ferroelectric Field Effect Transistor for Nonvolatile Memory Applications

Abstract: Channel current conduction modulation with the spontaneous polarization of ferroelectric films in ferroelectric field-effect transistors (FeFETs) has been widely investigated. Low interface quality and thermodynamic instability owing to the presence of dangling bonds in the conventional ferroelectrics have limited the memory retention and endurance of FeFETs. This, in turn, prevents their commercialization. However, the atomically thin nature of 2D ferroelectric, semiconducting, and insulating films facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…The α‐In 2 Se 3 is known as one of the stable vdW ferroelectric materials at room temperature because of the interlocking 50,51 . A recent research confirmed that ferroelectricity of α‐In 2 Se 3 is maintained at over 10 4 s 55 . This ferro‐floating memory is not faster than the ferroelectric transistors for two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…The α‐In 2 Se 3 is known as one of the stable vdW ferroelectric materials at room temperature because of the interlocking 50,51 . A recent research confirmed that ferroelectricity of α‐In 2 Se 3 is maintained at over 10 4 s 55 . This ferro‐floating memory is not faster than the ferroelectric transistors for two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…InSe is used since it exhibits promising properties in the applications of 2D FET. [ 19–21 ] Eight 2D metals, including α‐graphyne, Cd 3 C 2 , Hg 3 C 2 , 1T‐TiSe 2 , 1T‐MoS 2 , Nb 2 CO 2 , Ta 2 CO 2 , and Nb 2 CF 2 were utilized in our study based on two selection rules: i) they should possess a wide range of work functions (4.55 to 6.29 eV in our study); and ii) they should have negligible metal‐induced gas states upon interaction with InSe.…”
Section: Resultsmentioning
confidence: 99%
“…InSe is used since it exhibits promising properties in the applications of 2D FET. [19][20][21] Eight 2D metals, including α-graphyne, Cd 3 C 2 , Hg 3 C 2 , 1T-TiSe 2 , 1T-MoS 2 , Nb 2 CO 2 , Ta 2 CO 2 , and Nb 2 CF 2 were…”
Section: Resultsmentioning
confidence: 99%
“…Normally, bulk perovskite, oxide, and organic ferroelectric polymers are used as the gate dielectrics in conventional Fe-FETs, which exhibit excellent nonvolatile characteristics, such as a 10 3 current on/off ratio in bulk gate black phosphorus/poly­(vinylidenefluoride- co -trifluoroethylene) [P­(VDF-TrFE)], optically rewritable 87% conductivity change in graphene/lead magnesium niobate-lead titanate, an ultrahigh current on/off ratio of 7 × 10 7 in graphene/BiFeO 3 , ultrasensitive negative capacitance in MoS 2 /Hf 0.5 Zr 0.5 O 2 . Currently, two-dimensional (2D) ferroelectric materials with atomically thin bodies have aroused extensive interest because of the absence of dangling bonds and the strong electrostatic control, ,, such as α-In 2 Se 3 , , CuInP 2 S 6 , , and InSe . 2D ferroelectric materials have also exhibited the strong modulating ability in the 2D channel conduction, which give potential for continuous scaling in both vertical and planar dimensions.…”
Section: Introductionmentioning
confidence: 99%